METHODOLOGY FOR THE DEVELOPMENT OF CREATIVE ACTIVITY OF STUDENTS IN PEDAGOGICAL UNIVERSITIES BASED ON THE INTEGRATION OF THEORY AND PLENER PRACTICE - Ibragimov Xurshid Xasanovich (Modern American Journals, 2025)
This article explores the development and application of a methodology aimed at developing students' creative activity based on the integration of theory and plenary practice in pedagogical universities. The study analyzes ways to improve the creative abilities of students through the use of a competency-based approach and innovative pedagogical technologies. Plenary practice is considered as an important tool in the development of students' artistic and aesthetic thinking. The results of the experiment show that the integration of theory and practice significantly improves the creative activity of students. The article provides practical recommendations for pedagogical educational institutions.
Keywords: Creative activity, plein air practice, theory-practical integration, creativity, pedagogical education, competency-based approach.